Perancangan Motion Graphic Pentingnya Sterilisasi Kucing Untuk Menstabilkan Populasi Kucing - Delya Nabilla Umairoh; Subari Subari; Rahmat Kurniawan (LPPM STIKI Malang, 2023)
The cat population is increasing every year, leading to many negative impacts on cats and the surrounding environment, such as an abundance of hungry cats due to food competition and injuries caused by some people feeling disturbed by their presence. Besides aiding by providing food or adopting cats, cat sterilization is considered more effective in addressing this issue. However, there are still many people who are unaware of the importance of cat sterilization, especially for cat owners. Therefore, the dissemination of education about the significance of cat sterilization is necessary, so that through motion graphics, the message about the importance of cat sterilization can be effectively conveyed to the wider community. Through research methods utilizing design thinking, as well as the exploration of concepts and the design process involving the integration of 2D illustrations, typography, and audio, a motion graphic is produced that helps the community understand the importance of cat sterilization. The research results indicate that motion graphics can serve as a medium to efficiently deliver messages that are engaging and have a broader reach among the public.